Conservation of Rhodococcus equi (Magnusson 1923) Goodfellow and Alderson 1977 and rejection of Rhodococcus hoagii (Morse 1912) Kämpfer et al. 2014. Issue 5 (24th April 2020) - Vázquez-Boland, José A.; Scortti, Mariela; Meijer, Wim G.
Abstract : A recent taxonomic study confirmed the synonymy of Rhodococcus equi (Magnusson 1923) Goodfellow and Alderson 1977 and Corynebacterium hoagii (Morse 1912) Eberson 1918. As a result, both R. equi and C. hoagii were reclassified as Rhodococcus hoagii comb. nov. in application of the principle of priority of the Prokaryotic Code. Because R. equi is a well-known animal and zoonotic human pathogen, and a bacterial name solidly established in the veterinary and medical literature, we and others argued that the nomenclatural change may cause error and confusion and be potentially perilous. We have now additionally found that the nomenclatural type of the basonym C. hoagii, ATCC 7005 T, does not correspond with the original description of the species C. hoagii in the early literature. Its inclusion as the C. hoagii type on the Approved Lists 1980 results in a change in the characters of the taxon and in C. hoagii designating two different bacteria. Moreover, ATCC 7005, the only strain in circulation under the name C. hoagii, does not have a well documented history; it is unclear why it was deposited as C. hoagii and a possible mix-up with a Corynebacterium ( Rhodococcus ) equi isolate is a reasonable assumption. We therefore request the rejection of Rhodococcus hoagii as a nomen ambiguum, nomen dubium and nomen perplexum in addition to nomen periculosum, and conservation of the name Rhodococcus equi, according to Rules 56ab of the Code.